Influence of parity and body condition score on response and conception rate of saanen cross by Estrus Synchronization with CIDR - Mira, Panadi (2015)
Fourteen Saanen cross with parity and BCS record were allocated in two groups where the first stage involved 6 does and 8 does in following stages. All does were subjected to 14-days CIDR treatment containing 0.3 g progesterone followed by subcutaneous injection of 5ml catosal and 5ml ferriade. After 23 h of CIDR withdrawal, buck was introduced from 9 am to 6 pm for 3 days duration to allow natural mating and the response observed visually. The result showed estrus response were not differ (p>0.05) between nulliparous (40%), primiparous (66.67%) and multiparous (40%) and only does within BCS 2.5-4.0 were response (77.78%). Additionally, interval from CIDR withdrawal to onset of estrus were not differ (p>0.05) between nulliparous (24.78±15.84h), primiparous (19.86±9.99h) and multiparous (24.85±13.13h) does and not differ (p>0.05) between BCS, where only does within BCS 2.5-4.0 were response with 36.95±9.47h interval and 8.12 ± 3.96h estrus duration. Estrus duration were not differ (p>0.05) between nulliparous (1.57±1.28h), primiparous (8.61±8.04h) and multiparous (6.57±5.18h) does. Parity and BCS influence expression of certain estrus sign (p<0.05). The most reliable sign were swollen/red vulva, restlessness and doe rub face/body to fixed object/ buck. There were no significant different between parity and BCS with conception rate (p>0.05) where nulliparous (60%), primiparous (33.33%) and multiparous (50%) and BCS<2.5 (33.33%) and BCS=2.5-4.0 (66.67%). As conclusion, CIDR program 100% successful in synchronizing estrus in does. Parity and BCS of does not influence estrus response, onset of estrus, estrus duration and conception rate but influenced on certain estrus sign.